Mapping factors influencing initiation of antiretroviral treatment among adolescents living with HIV/AIDS in sub-Saharan Africa: A scoping review protocol. - Palesa Grace Likoti; Desmond Kuupiel; Nelisiwe Khuzwayo (PLoS ONE)
Background Since the Start Free, Stay Free, and AIDS-Free launch, UNAIDS targets intended to promote interventions to prevent HIV transmission and promote access to ART among adolescents and children, of which none were achieved in 2020. In the sub-Saharan African region, the number of adolescents initiated on ART drugs remained consistently low, with approximately100 000 adolescents succumbing to AIDS-related causes in 2022. Although HIV prevalence among adolescents had been reduced, several HIV- positive adolescents died without being initiated on ART drugs. Therefore, this scoping review protocol aims to map factors influencing the initiation of ART drugs among adolescents living with HIV in sub-Saharan Africa. Methods The methodological framework for scoping reviews will guide this scoping protocol. A search strategy will be used to search literature in electronic databases, including EBSCOhost (PubMed/MEDLINE), Google Scholar, Science Direct, Scopus, BioMed Central, and the World Health Organization library for citations and literature using keywords and the Medical Subjects Heading (MeSH). The electronic databases will be supplemented by hand-searching references on the included studies. The search will be from Jan 01, 2012, to Dec 31, 2022. Articles will be searched and assessed for eligibility by two screeners uploaded on the Endnote software, and duplicates will be identified and removed before the abstract screening. The two screeners will assess the eligibility of the abstracts and the complete articles of the selected studies using the inclusion and exclusion criteria. A third screener will intervene when there is a lack of consensus between the two screeners. The selection process will be documented by following and using the PRISMA flow diagram (Fig 1). A thematic content analysis will present a narrative account of the extracted data. Discussion The results of this review will identify and describe factors influencing the initiation of Antiretroviral treatment among adolescents living with HIV in the Sub-Saharan African region. The findings will guide future research and inform tailored interventions and strategies for initiating ART among adolescents. Trial registration Open Science Framework. https://doi.org/10.17605/OSF.IO/RNF2T.